2016
DOI: 10.1016/j.jtcvs.2016.01.061
|View full text |Cite
|
Sign up to set email alerts
|

A modified technique of laryngotracheal reconstruction without the need for prolonged postoperative stenting

Abstract: We conclude that this modified technique of laryngotracheal reconstruction represents a valid treatment option for patients with complex glottosubglottic stenosis, avoiding the need for prolonged postoperative stenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…For glottosubglottic stenosis with a side-to-side narrowing, a laryngotracheal reconstruction technique with rib cartilage grafting was applied. 8 Bronchoscopy was routinely performed at the end of surgery and based on clinical need during the hospital stay.…”
Section: Surgical Techniquementioning
confidence: 99%
“…For glottosubglottic stenosis with a side-to-side narrowing, a laryngotracheal reconstruction technique with rib cartilage grafting was applied. 8 Bronchoscopy was routinely performed at the end of surgery and based on clinical need during the hospital stay.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Although satisfactory outcomes, the technique carries the disadvantage of postoperative stenting. A modification of Couraud’s technique was developed by the Vienna Laryngotracheal Team ( 8 ). Despite the complexity of such a reconstruction the functional outcome was excellent in all of the five initially reported cases.…”
Section: Surgical Techniques and Functional Outcomesmentioning
confidence: 99%
“…In experienced hands, laryngotracheal surgery can be performed with only a minimal impact on glottic functions. We and others have shown that the best results can be obtained in patients primarily referred to surgery (8,9). Pre-treated patients usually require more extended surgical techniques and functional outcomes are worse than in previously untreated patients (6,7).…”
Section: Introductionmentioning
confidence: 97%
“…For management of glottic and subglottic problems, laryngotracheal reconstructions using rib cartilage grafts were developed by Cotton [3] and Monnier [4] (pediatric patients) and by Couraud [5] (adults). Whereas these complex reconstructions required an internal stenting (Montgomery T tube, LT-Mold), recent adaptations of the technique facilitate a single-stage repair [6].…”
mentioning
confidence: 99%